2016
DOI: 10.1080/09513590.2016.1188378
|View full text |Cite
|
Sign up to set email alerts
|

Which are the most common thrombophilic genetic nucleotide polymorphisms in infertile women undergoing an IVF cycle?

Abstract: Our results showed an increased frequency of genetic nucleotide polymorphisms in women reporting failures in IVF techniques. Differently from scientific literature data, in our work, the most frequent mutation affects the enzyme gene MTHFR, particularly the C667T mutation; on the other side, mutations of factor V and II are less common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These results were in accordance with Gulino, 15 who found MTHFR gene mutation in most infertile patients selected for thrombophilia screening. The number of mutations for each patient is not detailed, since, according to Patounakis, 16 outcomes cannot be predicted by the cumulative number of thrombophilic mutations present in the patient.…”
Section: Resultssupporting
confidence: 92%
“…These results were in accordance with Gulino, 15 who found MTHFR gene mutation in most infertile patients selected for thrombophilia screening. The number of mutations for each patient is not detailed, since, according to Patounakis, 16 outcomes cannot be predicted by the cumulative number of thrombophilic mutations present in the patient.…”
Section: Resultssupporting
confidence: 92%
“…There is accumulating evidence that there is a connection between thrombophilia factor MTHFR and infertility of both men and women (1,3,(10)(11)(12)(16)(17)(18). In females, the C677T mutation in the MTHFR gene greatly increases the risk of miscarriage (1,3,11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…In females, the C677T mutation in the MTHFR gene greatly increases the risk of miscarriage (1,3,11,(16)(17)(18). As far as males with azoospermia are concerned, there is a high prevalence of the MTHFR C677T mutation in comparison to fertile controls (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent findings have described a negative feedback function of MTHFR C677T mutation in the coordination of follicle development. In a study composed of 262 women undergoing a fresh cycle of IVF with ICSI, the polymorphism frequency of related genes, for example, the ACE and PAI-1 genes, especially the most common mutation of the MTHFR gene C667T, were found to be increased in women reporting failures in IVF techniques (21). Pavlik et al (22) indicated that the MTHFR 677TT genotype is associated with higher serum AMH concentrations and has a negative effect on numbers of oocytes retrieved in 270 women undergoing COH for IVF.…”
mentioning
confidence: 99%